Existence and regularity of 1D-solitons for a hyperelastic dispersive model (2015)
We show the existence, regularity and analyticity of one-dimensional solitons for a dispersive type equation that models the deformations of a hyperelastic compressible plate. We follow a variational approach by characterizing solitons as critical points of a suitable functional. Our method involves the Mountain Pass Theorem.